DUA MATA MEMANDANG KARHUTLA (ANALISIS FRAMING PEMBERITAAN KARHUTLA DI THE STAR DAN KOMPAS.COM MODEL ROBERT N. ENTMAN) - Chelsea Andriany; Novelia Wijayanti; Miletresia Miletresia; Kho Gerson Ralph Manuel (Universitas Bunda Mulia, 2019)
ABSTRACTForest and Land Fire Disasters (KARHUTLA) recurrently occur in Indonesia every year, especially in the dry season. In addition to numerous places in Indonesia, neighboring country like Malaysia also got affected by the after effects of KARHUTLA: smog. As a result, Smog has greatly been a concerned issue of both Malaysian and Indonesian media. While both of the media reporting on the same issue, fundamentally both media have different perspectives representing both countries; none of them wants to be held as solely responsible party that triggered the disaster. News framing that has been applied by the media to speak for their subjective objectivity shapes a distinct perception of reality among their audiences as a consequence. This is what makes researchers interested in analyzing more deeply the description and phenomenon of KARHUTLA reporting by using a descriptive qualitative research method. This study uses the Robert N. Entman framing analysis model as a tool to dissect media coverage of KARHUTLA issues from their respective perspectives. On the basis of research conducted by researchers, the online news portal The Star Malaysia and Kompas.com Indonesia were established as research subjects. While the object of this research is the news related to KARHUTLA. The results of the framing analysis show that there are media efforts to shape the perception of the reality of the states of Indonesia and Malaysia that are